Forensic Linguistics: Analysis of Language in Legal Contexts, Including Plagiarism, Legal Documents, and Defamation - admin, admin (English Language, Linguistics, Literature, And Education Journal, 2025)
The study of forensic linguistics is not a simple task since a linguist must have knowledge in other fields to support their expertise in linguistics to become an expert witness. Even though the testimony provided by a linguist is in the field of linguistics, in investigating or analysing a case, a linguist requires other skills such as computerisation, knowledge of a region's culture, and so on. With the development of forensic linguistics as a discipline, linguistic studies are very much needed. This study attempts to discuss some examples of forensic linguistic cases. The research method used in this study is descriptive, as it focuses on the analysis of language in forensic linguistics. Both spoken and written forms are the two types of data that are the objects of this research. The results of this study show both spoken and written data related to language in legal processes, language in legal products, and language in legal evidence. The discussion of the aspects of the language analysis dimension that are typical in forensic linguistics, namely comparative and distinguishing dimensions, is expected to contribute insights for the development of forensic linguistic studies. It is also hoped that the results of the discussion in this study can enrich the material for linguistic expert testimony in legal cases.